Structure and mechanism of the T-box riboswitches - Zhang, Jinwei (Wiley Interdiscip Rev RNA, 2015)
In most Gram-positive bacteria, including many clinically devastating pathogens from genera such as Bacillus, Clostridium, Listeria and Staphylococcus, T-box riboswitches sense and regulate intracellular availability of amino acids through a multipartite mRNA-tRNA interaction. The T-box mRNA leaders respond to nutrient starvation by specifically binding cognate tRNAs and sensing whether the bound tRNA is aminoacylated, as a proxy for amino acid availability. Based on this readout, T-boxes direct a transcriptional or translational switch to control the expression of downstream genes involved in various aspects of amino acid metabolism: biosynthesis, transport, aminoacylation, transamidation, etc. Two decades after its discovery, the structural and mechanistic underpinnings of the T-box riboswitch were recently elucidated, producing a wealth of insights into how two structured RNAs can recognize each other with robust affinity and exquisite selectivity. The T-box paradigm exemplifies how natural non-coding RNAs can interact not just through sequence complementarity, but can add molecular specificity by precisely juxtaposing RNA structural motifs, exploiting inherently flexible elements and the biophysical properties of post-transcriptional modifications, ultimately achieving a high degree of shape complementarity through mutually induced fit. The T-box also provides a proof-of-principle that compact RNA domains can recognize minute chemical changes (such as tRNA aminoacylation) on another RNA. The unveiling of the structure and mechanism of the T-box system thus expands our appreciation of the range of capabilities and modes of action of structured non-coding RNAs, and hints at the existence of networks of non-coding RNAs that communicate through both, structural and sequence specificity.